HmSOD1 gene mutation‐induced disturbance in iron metabolism is mediated by impairment of Akt signalling pathway. Issue 3 (29th January 2018) - Halon‐Golabek, Malgorzata; Borkowska, Andzelika; Kaczor, Jan J.; Ziolkowski, Wieslaw; Flis, Damian J.; Knap, Narcyz; Kasperuk, Kajetan; Antosiewicz, Jedrzej
Abstract: Background: Recently, skeletal muscle atrophy, impairment of iron metabolism, and insulin signalling have been reported in rats suffering from amyotrophic lateral sclerosis (ALS). However, the interrelationship between these changes has not been studied. We hypothesize that an impaired Akt–FOXO3a signalling pathway triggers changes in the iron metabolism in the muscles of transgenic animals. Methods: In the present study, we used transgenic rats bearing the G93A hmSOD1 gene and their non‐transgenic littermates. The study was performed on the muscles taken from animals at three different stages of the disease: asymptomatic (ALS I), the onset of the disease (ALS II), and the terminal stage of the disease (ALS III). In order to study the molecular mechanism of changes in iron metabolism, we used SH‐SY5Y and C2C12 cell lines stably transfected with pcDNA3.1, SOD1 WT and SOD1 G93A, or FOXO3a TM‐ER. Results: A significant decrease in P‐Akt level and changes in iron metabolism were observed even in the group of ALS I animals. This was accompanied by an increase in the active form of FOXO3a, up‐regulation of atrogin‐1, and catalase. However, significant muscle atrophy was observed in ALS II animals. An increase in ferritin L and H was accompanied by a rise in PCBP1 and APP protein levels. In SH‐SY5Y cells stably expressing SOD1 or SOD1 G93A, we observed elevated levels of ferritin L and H and non‐haem iron. Interestingly, insulin treatment significantly down‐regulated ferritin L and H proteins in the cell. Conversely, cells transfected with small interfering RNA against Akt 1, 2, 3, respectively, showed a significant increase in the ferritin and FOXO3a levels. In order to assess the role of FOXO3a in the ferritin expression, we constructed a line of SH‐SY5Y cells that expressed a fusion protein made of FOXO3a fused at the C‐terminus with the ligand‐binding domain of the oestrogen receptor (TM‐ER) being activated by 4‐hydroxytamoxifen. Treatment of the cells with 4‐hydroxytamoxifen significantly up‐regulated ferritin L and H proteins level. Conclusions: Our data suggest that impairment of insulin signalling and iron metabolism in the skeletal muscle precedes muscle atrophy and is mediated by changes in Akt/FOXO3a signalling pathways.